Anesthesia‐related neurotoxicity and the developing animal brain is not a significant problem in children. Issue 1 (30th September 2014) - Hansen, Tom G.; Morton, Neil
Summary A multitude of animal studies have shown that virtually all general anesthetics used in clinical practice possibly during a vulnerable period of brain development (i.e., brain growth spurt, peak of synaptogenesis) may lead to neurodegeneration (particularly apoptosis) and abnormal synaptic development with functional deficits in learning and behavior later in life. Initial studies were mainly performed in immature rodent pups, but more recent studies have included nonhumans primates (rhesus monkeys). Given the number of neonates, infants, and young children anesthetized annually worldwide, these findings could have significant public health implications. So far, relatively few human (cohort) studies focusing on this topic have been published with inconsistent results. While some studies have indicated an association between exposure to anesthesia and surgery, other studies have indicated no such association. Prospective studies are underway, but the result will not be available for several years. This paper reviews some of the preclinical background behind anesthesia‐related neurotoxicity but focuses mainly on the human studies so far. It is concluded that although disturbing, the animal data lack verification in humans. Fortunately, the humans studies performed so far have been unable to confirm these animal data. A single brief anesthetic seems safe in infants. Multiple anesthetic and surgical exposures on the other hand are different. But there may be other reasons for this than merely the anesthetics. Currently, there is no need to change current anesthetic clinical practice or to postpone or cancel truly urgent surgeries in young children.